Moral agency in Eastern and Western thought perspectives on crafting character - Jacobs, Jonathan A. 1955-; Meyer, Heinz-Dieter (Routledge, 2025)
"This volume explores how individuals use moral agency to craft the moral dispositions and moral capabilities needed for living well-lived lives. It draws on Eastern and Western philosophical and ethical traditions to formulate and address key issues concerning character development and moral agency. In both Eastern and Western traditions, the complexities of shaping an individual's moral agency focus on sustained processes of inner self-cultivation. The chapters in this volume highlight the ways in which one is to manage and direct one's desires and aspirations, and what is to count as the source of guidance for a well-lived life. They engage with key figures and traditions in the history of Eastern and Western philosophy including Confucian, Buddhist, and western sources from Aristotle to Kant. The juxtaposition of sources from the different parts of the world highlights striking similarities and significant contrasts and provides rich conceptual resources for further exploration of these issues. The volume provides a broader, deeper pursuit of central issues of moral psychology and ethics in ways that highlight the inexhaustible resources in these traditions. The focus on character is a way to draw together perspectives on ethical life, theories of human agency, views of fundamental, life-guiding values, and relations between individuals and society and how persons see their place in the world. Moral Agency in Eastern and Western Thought will appeal to scholars and advanced students working on virtue ethics, moral psychology, comparative philosophy, and history of philosophy"--
Keywords: Moralisches Handeln; Ethik; Interkulturelle Philosophie; Charakter; Ethics, Comparative; Philosophy, Comparative; East and West; Morale comparée; Philosophie comparée; Aufsatzsammlung